PEMODELAN MORTALITA DENGAN FAKTOR UNDERWRITING DAN FRAILTY MENGGUNAKAN GENERALIZED LINEAR MIXED MODELS DAN APLIKASINYA DALAM MENENTUKAN HARGA PREMI - ROHMAN, SITI ALFIATUR ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Underwriting is a process to classify risk levels of the insurance participant based on certain factors that is called underwriting factor. Underwriting can be a consideration to decide whether the insurance application of applicant is received or rejected. Underwriting factors is observed factors, while frailty is unobserved factors as susceptibility of death risk. Both of this value obtained by Generalized Linear Mixed Models (GLMM) method and they are used to mortality modelling. Underwriting factors is assumed binomial and frailty is normal. Mortality models is used to count premium of each participant in the certain age.